Person Deixis in EFL Classroom Interaction: A Comparative Pragmatic Study of Kazakhstani and Indonesian Students - Arbain Arbain (Borneo Educational Journal (Borju), 2026)
This study examines person deixis in EFL classroom interaction through a comparative pragmatic analysis of Kazakhstani and Indonesian students. The research aimed to identify the person deictic expressions used in classroom discussion and to analyze their pragmatic functions in interaction. A qualitative comparative design was employed with simple frequency support. The participants were 20 students enrolled in a Pragmatics course at an Indonesian university, consisting of five Kazakhstani and fifteen Indonesian students. Data were collected through audio-recorded group discussions across three classroom meetings and transcribed verbatim for analysis. The findings show that first person singular was the most frequently used form, followed by first person plural, second person, and third person plural. Pragmatically, person deixis functioned to express personal stance, build solidarity, engage listeners, manage interaction, and refer to external groups. The study highlights that person deixis operates not only as a grammatical category but also as a pragmatic resource for meaning construction in multilingual EFL classroom interaction.